Aspéctos socioeconômicos e identificação molecular de peixes ornamentais da família Loricariidae (Siluriformes) comercializados em Santarém-PA - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
The Tapajós River is one of the main clear water rivers that make up the Amazon basin. It is characterized by sediment-poor waters and a large number of waterfalls and rapids. Large projects related to agribusiness, mining, dam construction and infrastructure pose strong threats to their physical and environmental structure, as well as to the associated aquatic biota. The reophilic fish of the family Loricariidae, are adapted to the common lotic and stone environments of the medium and high Tapajós. They have a confusing subfamilial taxonomy and many species that are not yet formally described by science are released for commercial purposes, which certainly hinder conservation and enforcement actions. These organisms constitute an important natural resource that supports a productive chain of ornamental fish for the national and international aquarium market. Projects aiming at the Tapajós river hydroelectric development in the Itaituba region foresee the construction of dams and immediate modification of the natural habitat of these fish. The aim of the present study is to describe the socioeconomic and molecular genetic patterns of ornamental fish of the Loricariidae family of the Tapajós River aiming at a better understanding of the biodiversity and to contribute to the resolution of taxonomic problems and the sustainable management of this natural resource. For the socioeconomic analysis, data were obtained from the Animal Transport Guides (GTA) and Fish Transit Guides for Ornamental and Aquaristic purposes (GTPON), covering the period from January/2013 to December/2016. For genetic characterization, DNA barcoding molecular taxonomic markers were developed for the most commercialized species in the Tapajós River region in Santarém-PA. A total of 136,705 examples were sold, generating gross revenue of R$ 365,013.80. The species Baryancistrus sp. (LDA33), Hypancistrus sp. (L260), Pseudacanthicus sp. (L273) and Peckoltia compta (L134) are the most productive and economically profitable, accounting for 59.6% of gross revenue generated from January 2013 to December 2016. 29 DNA barcode sequences over 500 bp were produced without stop codons or indels. The base composition showed an average percentage of 17.57% (G), 25.29% (C), 25.22% (A) and 31.92% (T). Barcoding DNA analysis confirmed the identification of 9 species with an average intraspecific divergence of 0.24%. Given the enormous diversity of the Amazonian ichthyofauna, greater efforts are recommended to increase the public reference collection of DNA barcoding molecular labels.
Keywords: Rio Tapajós; Loricariidae; Aquariofilia; DNA Barcoding.; CNPQ::CIÊNCIAS AGRÁRIAS; RECURSOS NATURAIS, BIODIVERSIDADE E BIOPROSPECÇÃO NA AMAZÔNIA